TIME BUDGET PRESSURE MEMODERASI PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT - Devi, Luh Mahatma Setya; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
800x600 This study aimed to test time budget pressure moderating influence of personal characteristics auditor on acceptance of dysfunctional audit behavior. The sampling method using saturated sampling technique in which all members of the population used as a sample. The data in this study were collected by distributing a questionnaire to be filled or answered by the respondent auditor in KAP in Denpasar. Researchers use moderated regression analysis (MRA) as hypothesis testing. Results of this study stated that the personal characteristics of the auditor on acceptance of dysfunctional audit behavior positive effect. Time budget pressure and acceptance of dysfunctional audit behavior has no direct influence. Additionally time budget pressure is able to strengthen the influence of personal characteristics auditor on acceptance of dysfunctional audit behavior. Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4
Keywords: Acceptance of dysfunctional audit behavior, characteristics personal auditors, time budget pressure